A. Seminar on education managementt for tecnichal education 23-24 March at FPTK IKIP Padang Sumbar - A. Seminar on education managementt for tecnichal education 23-24 March at FPTK IKIP Padang (IKIP)
ii, 92 p.; 29 cm.